Two‐dimensional antiscatter grid: A novel scatter rejection device for Cone‐beam computed tomography. Issue 2 (8th January 2018) - Alexeev, Timur; Kavanagh, Brian; Miften, Moyed; Altunbas, Cem
Abstract : Purpose: Scattered radiation remains to be a major cause of image quality degradation in Flat Panel Detector (FPD)‐based Cone‐beam computed tomography (CBCT). We have been investigating a novel two‐dimensional antiscatter grid (2D‐ASG) concept to reduce scatter intensity, and hence improve CBCT image quality. We present the first CBCT imaging experiments performed with the 2D‐ASG prototype, and demonstrate its efficacy in improving CBCT image quality. Methods: A 2D‐ASG prototype with septa focused to x‐ray source was additively manufactured from tungsten and mounted on a Varian TrueBeam CBCT system. CBCT projections of phantoms were acquired with an offset detector geometry using TrueBeam's "developer" mode. To minimize the effect of gantry flex, projections were gain corrected on angle‐specific bases. CBCT images were reconstructed using a filtered backprojection algorithm and image quality improvement was quantified by measuring contrast‐to‐noise ratio (CNR) and CT number accuracy in images acquired with no antiscatter grid (NO‐ASG), conventional one dimensional antiscatter grid (1D‐ASG), and the 2D‐ASG prototype. Results: A significant improvement in contrast resolution was achieved using our 2D‐ASG prototype compared to results of 1D‐ASG and NO‐ASG acquisitions. Compared to NO‐ASG and 1D‐ASG experiments, the CNR of material inserts improved by as much as 86% and 54% respectively. Using 2D‐ASG, CT number underestimation in water equivalent material section of the phantom was reduced by up to 325 HU when compared to NO‐ASG and up to 179 HU when compared to 1D‐ASG. Conclusion: We successfully performed the first CBCT imaging experiments with a 2D‐ASG prototype. 2D‐ASG provided significantly higher CT number accuracy, higher CNR, and diminished scatter‐induced image artifacts in qualitative evaluations. We strongly believe that utilization of a 2D‐ASG may potentially lead to better soft tissue visualization in CBCT and may enable novel clinical applications that require high CT number accuracy.